Personal ethos in the literature of Slovak and Czech dissidents - Bátorová, Mária (Primerjalna književnost, 2010)
This article discusses texts by selected authors from the period of "consolidation" in Czechoslovakia. The first part briefly outlines the sociohistorical context of dissident writing.
Keywords: književnost; literature; ethics; etika; Czech literature; češka književnost; Slovak literature; slovaška književnost; disidentstvo; disidentski pisatelji; družbena vloga; esej